Sistem Pendukung Keputusan (SPK) Karyawan Tetap PT. Global Autoparts Pratama dengan Metode TOPSIS - Asal, Oswaldus; Prayudhi, Risa; Riesmiyantiningtias, Ninuk; Ramadhani, Anjas (Jurnal Teknologi Terpadu, 2025)
PT. Global Autoparts is a company engaged in the distribution of car spare parts, the selection process for permanent employees still uses an assessment form. The purpose of this study is to determine the permanent employees who are in the first ranking order. The TOPSIS method is used because of its simple and easy-to-understand mathematical concept, its computational efficiency and its ability to measure the relative performance of decision alternatives into a simple mathematical form. The TOPSIS method uses ranking based on the results of the assessment form, so the system no longer needs to sort the data from the largest to the smallest values during the value data processing process and the results presented by the system can be printed in the form of a report. The final result of the selection value in determining the permanent employees who are in the first ranking order, namely A03 named "Paulina" with a preference value of 0.648 who gets the highest preference result value (Vi). The conclusion states that the employee named "Paulina" is entitled to become a permanent employee at PT. Global Autoparts Pratama from the 10 employee data that have been selected.